(3QSGdI aj JMOjO GdfaS GdMjhGfjIs
(3ChdgG (B:s
(3GSJNQJ Gddg hGLH GdhLhO haGFV GdLhO eG djS gi ai eGOI GdfGWbI s
(3BNQgG (B:s
(3hMGdI GfHYGJgG Yfg JSei QhMkG MjhGfjkG agPG gh JYOjO Gdbhi GdHGWfI hGdXGgQI ddfaS GdMjhGfjI hPdc eG GQOfG Cf fHjf hGdMeO ddg QH GdYGdejf s
(3HBNQgG fbhd cKjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(343(3)) s
Keywords: (3GdadSaI hGdefWbs